Assessment of the quality of water in Johore Straits - Ong, Peik Looi. (2008)
The Strait of Johore separates the island of Singapore from Peninsular Malaysia. A causeway, 500m long, bridges the two countries and divides the strait into western and eastern sections. As a result, the water in the vicinity of the causeway is generally quiescent. The primary hydrodynamic force acting on this semi-enclosed body of water is tidal in nature. The tidal regime is one of mixed tide, with predominant diurnal tides. The tidal range fluctuates within 2-2.5m, rising up to 3m during spring tides. The characteristics of these tidal movements significantly influence the transport features of pollutants into the Strait of Johore.